Genetics and heterosis of quality and yield of pumpkin - Pandey, Sudhakar; Jha, Aastik; Kumar, Sanjeev; Rai, Mathura (Indian Journal of Horticulture, 2010)
Gene action, combining ability and heterosis for quality and yield attributes in pumpkin was studied involving 21 cross combinations obtained from seven diverse inbreds in half-diallel fashion for four characters. The analysis revealed that none of the parents was a good general combiner for all the characters consistently; however, the parent, pumpkin-172 was good combiner for flesh thickness, total carotenoids and yield. The parents, IVPK-226 and BP-18 appeared to be good general combiners for ascorbic acids content. The gca variances were higher than the sca variances for flesh thickness, total carotenoids and ascorbic acid, while yield per plant had gca variances lower than the sca variances indicating the pre-dominance of non-additive gene effects for yield and additive gene action for flesh thickness, total carotenoids and ascorbic acid. The cross Pumpkin-172 × Pumpkin-105 exhibited highest sca estimates for flesh thickness, total carotenoids and yield, while the combination, IVPK-226 × Pumpkin- 172 exhibited significant sca estimate for ascorbic acid content. The maximum heterosis for yield and ascorbic acid was exhibited by BS-165 × VRPG-7, whereas, BP-18 × Pumpkin-105 showed the maximum heterosis for total carotenoids. The study revealed that for improvement of traits like flesh thickness, total carotenoids and ascorbic acid, selections could be made, while fruit yield may be improved through hybridization.